Knowledge and Practice of Breast Self-Examination among Female Community Health Volunteers in Dharan Sub-Metropolitan City, Province No. 1, Nepal - Thapa, Kala; Rai, Gayatri; Shrestha, Mangala; Pokharel, Nirmala (Journal of BP Koirala Institute of Health Sciences, 2022)
Background: Regular breast self-examination is the most cost-effective method for the early detection of breast cancer. Female community health volunteers (FCHVs) could play an important role in teaching the community about breast self-examination (BSE). We aimed to assess the knowledge and practice of breast self-examination among FCHVs.Methods: Descriptive cross-sectional study was conducted using the census sampling method to select FCHVs from all 20 wards of Dharan sub-metropolitan city. Face-to-face interview was conducted using a semi-structured questionnaire to collect information related to the knowledge of BSE from consenting participants. The practice of BSE was assessed through direct observation of BSE by using a checklist. Descriptive and inferential statistical analysis was done using SPSS version 10.0. The level of significance was set at 0.05.Results: A total of 95 FCHVs (out of 107) were enrolled in the survey. The mean age (SD) of the study participants was 42.45 (8.97) years; 85.3% were married and majority (64.2%) had completed secondary level of education. The majority of the FCHVs, 65 (68.4%), earned monetary income less than NPR.7000.00 per month. The majority, 82 (86.3%), of the FCHVs had adequate knowledge but only 21 (22.2%) respondents had ever practiced BSE. No significant association was found between the knowledge and practice of BSE with the selected demographic variables such as age, marital status, educational level, age at menarche, and menopause.Conclusion: The FCHVs had adequate knowledge but poor practice regarding BSE. Training should be emphasized to improve their practice of BSE.